The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep43078
|View full text |Cite
|
Sign up to set email alerts
|

Direct binding of MEK1 and MEK2 to AKT induces Foxo1 phosphorylation, cellular migration and metastasis

Abstract: Crosstalk between the ERK cascade and other signaling pathways is one of the means by which it acquires its signaling specificity. Here we identified a direct interaction of both MEK1 and MEK2 with AKT. The interaction is mediated by the proline rich domain of MEK1/2 and regulated by phosphorylation of Ser298 in MEK1, or Ser306 in MEK2, which we identified here as a novel regulatory site. We further developed a blocking peptide, which inhibits the interaction between MEK and AKT, and when applied to cells, aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…Among all miRNAs, miR‐497 has been recognized as a tumor‐associated miRNA in breast cancer, colorectal carcinoma, and lung cancer, but the biological function of it in CC is not defined (Gu et al, ; Hu, Xu, & Ge, ; Jiang, Meng, Qi, Shen, & Sun, ). Now, we have already known that RAF‐1 was identified as one of the novel direct targets of miR‐195 and miR‐497, and that the extracellular signal‐regulated kinase 1 (ERK1) was one of the major signaling pathways which activate in a large number of cells (Li et al, ; Procaccia, Ordan, Cohen, Bendetz‐Nezer, & Seger, ). Mitogen‐activated protein kinase (MAPK) signaling pathway participated in tumor development, in which RAF‐1 and ERK1/2 are of great importance (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among all miRNAs, miR‐497 has been recognized as a tumor‐associated miRNA in breast cancer, colorectal carcinoma, and lung cancer, but the biological function of it in CC is not defined (Gu et al, ; Hu, Xu, & Ge, ; Jiang, Meng, Qi, Shen, & Sun, ). Now, we have already known that RAF‐1 was identified as one of the novel direct targets of miR‐195 and miR‐497, and that the extracellular signal‐regulated kinase 1 (ERK1) was one of the major signaling pathways which activate in a large number of cells (Li et al, ; Procaccia, Ordan, Cohen, Bendetz‐Nezer, & Seger, ). Mitogen‐activated protein kinase (MAPK) signaling pathway participated in tumor development, in which RAF‐1 and ERK1/2 are of great importance (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The FOXO transcription factors are considered to be tumor suppressors that inhibit cell proliferation and induce apoptosis ( 21 ). Indeed, FOXO1 plays multiple roles in various types of human cancers, including skin ( 23 ), liver ( 24 ) and breast cancer ( 25 ). An increasing number of studies have linked the tumor suppressor activity of FOXOs to the regulation of genes involved in cell death (e.g., Fasl) ( 26 ) and cell cycle arrest (e.g., p27 KIP1 ) ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture experiments demonstrated that FOXO1 overexpression by transfection of the FOXO1‐AAA mutant gene suppresses NF‐κB signaling and gastric carcinogenesis . At the molecular level, Procaccia's group discovered that direct binding of MEK1 and MEK2 to Akt induces FOXO1 phosphorylation and thus contributes to cell migration and metastasis in a mouse breast cancer model . These findings all demonstrate that low levels/activity of FOXO1 is a possible factor for early carcinogenesis, and activated FOXO1 can inhibit carcinogenesis (Figs.…”
Section: Foxo1 and Carcinogenesismentioning
confidence: 97%
“…Previous studies have demonstrated that low levels or activity of FOXO1 have a close relationship with tumorigenesis. 34,35 FOXO1 silencing is related to suppressed EMT in A549 lung adenocarcinoma epithelial cells, which is evidenced by decreased epithelial markers (E-cadherin) and enhanced mesenchymal markers (SNAIL, SLUG). 36 Helicobacter pylori infection is the major risk factor for gastric cancer.…”
Section: Foxo1 and Carcinogenesismentioning
confidence: 99%